2018
DOI: 10.1175/bams-d-16-0254.1
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Sea Ice and Polar Emissions of Marine Biogenic Aerosols

Abstract: Accurate estimation of the climate sensitivity requires a better understanding of the nexus between polar marine ecosystem responses to warming, changes in sea ice extent, and emissions of marine biogenic aerosol (MBA). Sea ice brine channels contain very high concentrations of MBA precursors that, once ventilated, have the potential to alter cloud microphysical properties, such as cloud droplet number, and the regional radiative energy balance. In contrast to temperate latitudes, where the pelagic phytoplankt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 130 publications
7
56
1
Order By: Relevance
“…Wind erosion of frost flowers high in extracellular polysaccharides may offer a direct dispersal mechanism (Bowman and Deming, 2010) by which marine gel particles become airborne. Frost flower erosion and sea-ice brine extrusions to water and air during freeze-up are mechanisms by which fluxes of marine biological particles to the atmosphere might be coupled with extensive first-year sea-ice formation in autumn and winter (Gabric et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Wind erosion of frost flowers high in extracellular polysaccharides may offer a direct dispersal mechanism (Bowman and Deming, 2010) by which marine gel particles become airborne. Frost flower erosion and sea-ice brine extrusions to water and air during freeze-up are mechanisms by which fluxes of marine biological particles to the atmosphere might be coupled with extensive first-year sea-ice formation in autumn and winter (Gabric et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The Arctic summer possesses quintessential conditions for proliferation of primary productivity when open water and daylight hours are at their maxima . In a recent study, Gabric et al (2018) demonstrate a clear connection between sea ice extent, productivity, and marine biogenic aerosols. Additionally, recent modeling work has demonstrated that marine organic aerosols lead to increases in cloud ice in polar regions during the summer (Huang et al, 2018) link such sources to the air above.…”
Section: Introductionmentioning
confidence: 96%
“…Mapping can be focused on a particular region such as the Arctic or Southern Ocean. This feature should prove especially useful in the current era of rapid polar environmental change [58]. Plots can be extended downward in semi-arbitrary sections anywhere on the planet.…”
Section: Methodsmentioning
confidence: 99%